2015
DOI: 10.1134/s1070428015110184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of 2-cyanoethoxy derivatives of dammarane triterpenoids

Abstract: Abstract-Cyanoethylation of dammaran-3β-ols and 3-oxime dammarene, semisynthetic derivatives of the natural dipterocarpol, afforded a series of new dammarane triterpenoids containing 2-cyanoethoxy fragment at the carbon atom in the position 3 of the tetracyclic scaffold. A notable antiviral activity was found in 20(S)-3-[(2-cyanoethoxy)imino]-dammar-24-en-20-ol and 20(S)-3-О-(2-cyanoethyl)-25,26,27-trinor-20,24-olidedammarane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They are found frequently in many species of different plant families, including Euphorbiaceae, to which belongs the Croton genus. Some of the dammarane-type triterpenes are endowed with cytotoxic [51], antiviral [52], and antifungal [53] activities. A new dammarane type triterpene was isolated from Castenea mollisima showing potent α -glucosidase inhibition with an IC50 value of 0,1µM [54].…”
Section: α-Glucosidase Inhibition Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…They are found frequently in many species of different plant families, including Euphorbiaceae, to which belongs the Croton genus. Some of the dammarane-type triterpenes are endowed with cytotoxic [51], antiviral [52], and antifungal [53] activities. A new dammarane type triterpene was isolated from Castenea mollisima showing potent α -glucosidase inhibition with an IC50 value of 0,1µM [54].…”
Section: α-Glucosidase Inhibition Activitymentioning
confidence: 99%
“…A new dammarane type triterpene was isolated from Castenea mollisima showing potent α -glucosidase inhibition with an IC50 value of 0,1µM [54]. Dammarane-type compounds are naturally occurring triterpene saponins isolated from some species of Ginseng, and they have a variety of biological activities including anticancer and hepatoprotective effects [38,52]. To our knowledge, this is the first report for the in vitro inhibition of α -glucosidase by a known dammaran triterpene type (2) [55], isolated from Croton thurifer Additionally from the antidiabetic potential, tiliroside has been considered a dietary flavonoid because is contained in several edible plants and has demonstrated a variety of biological properties, including anticholinesterase, antiprotozoal, antioxidant, anti-inflamatory, hepatoprotective and moderate neuroprotective effect [49].…”
Section: α-Glucosidase Inhibition Activitymentioning
confidence: 99%
“…Dipterocarpol [(20S)-20-hydroxydammar-24-en-3-one] is the major metabolite of oleoresins of trees Dipterocarpus species [2]. Such chemical transformations of dipterocarpol as preparation of Nvinylpyrrolidone, γ-lactone, alkoxytetrahydrofuran, hydroxy-, epoxy-, oximino-,1,2,4-trioxolane,heterocyclic, 2-cyanoethoxy-, tetrazole as well as hybrid triterpenoid-steroid and derivatives were described [3][4][5][6][7][8][9]. It was demonstrated that dammarane triterpenoids possess anticancer [10], antiviral [11][12][13], immunostimulating [14] and anti-inflammatory [15] activities.…”
mentioning
confidence: 99%